1367. Management of Patients Presenting with Purulent Skin and Soft Tissue Infections in the Emergency Department (ED). (4th December 2021) - Son, Andrea; Hecker, Michelle
Abstract: Background: Incision and drainage (I&D) is the primary treatment for purulent skin and soft tissue infection (SSTI). Empiric adjunctive treatment of purulent SSTI targets methicillin-resistant Staphylococcus aureus (MRSA). In light of increasing antibiotic resistance, culture and sensitivity (C&S) from drained specimen and consideration of the local antibiogram are recommended. 1 Our primary objective was to assess the utilization of C&S from drained specimen in out institution's ED. Our secondary objectives were to describe antibiotic choice and duration of therapy upon discharge, to evaluate the appropriateness of antibiotic choice based on C&S and local antibiogram, and to assess the need for adjunctive antibiotic based on available literatures. Methods: A retrospective cohort study was performed on a random sample of unique patients who underwent I&D procedure in the ED from January 2019 through December 2019. Demographic and clinical data were collected from the electronic medical record. Results: Of 120 patients evaluated, only 14 patients (11.7%) had C&S performed on the initial I&D specimen (Table 1). Five patients received inappropriate antibiotic(s) based on C&S. Of 108 patients who were discharged from ED, antibiotic(s) was prescribed in 97 patients (Table 2). Mean duration of therapy was 7.8 days with 27.8% of patients prescribed a duration of therapy longer than 7 days. Despite high clindamycin resistant rate for MRSA (35%), clindamycin was the second most prescribed antibiotic. Adjunctive antibiotic(s) may have been unnecessary in 9.5% patients. Five patients reported possible adverse reaction related to prescribed antibiotic. Additional antibiotic course was prescribed in 15 patients for the same infection. Fifteen patients were readmitted to ED within 30 days and five of them required hospital admission Conclusion: At our institution, majority of patients were discharged after I&D with adjunctive antibiotic(s) without microbiologic testing. Despite high local clindamycin resistance, it was the second most commonly prescribed empiric treatment. Developing a clinical pathway that emphasizes the importance of timely microbiologic testing and local antibiogram consideration along with the need for appropriate adjunctive antibiotics may improve patient outcomes. Disclosures: All Authors : No reported disclosures